The Effectiveness of a Coordinated Response Toward Nonfatal Strangulation in Facilitating Evidence-Based Prosecution - Reckdenwald, Amy (Criminal justice policy review, 2021)
Many states’ laws now classify nonfatal strangulation as part of domestic violence as a felony offense, but prosecution of offenders remains challenging due to the nature of this type of violent offense. This study evaluates a coordinated effort designed to improve one county’s response to nonfatal strangulation. The impact of law enforcement training and specialized forensic medical examinations on facilitating evidence-based prosecution of nonfatal strangulation offenders is examined. Preliminary support is found for the effectiveness of the coordinated effort, highlighting the importance of comprehensive law enforcement training and detailed medical evidence in facilitating evidence-based prosecution.